A rare 4-fold interpenetrated metal–organic framework constructed from an anionic indium-based node and a cationic dicopper linker. Issue 19 (27th April 2021) - Pappuru, Sreenath; Idrees, Karam B.; Chen, Zhijie; Shpasser, Dina; Gazit, Oz M.
Abstract : We describe the synthesis and structure of a charged unique 4-fold interpenetrated MOF constructed from a new dicationic Robson-type dicarboxylate linker and a 4-connected In 3+ node. Abstract : A unique 4-fold interpenetrated metal–organic framework, TIF-1, was synthesized by combining an anionic indium node with a cationic linker. This framework shows a rare type of 4-fold interpenetrated dia network, constructed from tessellation of biangular and tetragonal type metal–organic micropores. The porosity of TIF-1 is moderate due to four-fold interpenetration and charge-balancing anions. The cationic feature of this MOF may give good efficiency for selective small anion exchange or separation. In addition, the thermal stability and moderate CO2 adsorption property of the complex were studied.